Isolation and Antagonistic Activity of Actinomycetes Associated with Strawberry Plants (Fragaria x ananassa Duch.) Against Colletotrichum acutatum Simmonds - Aji, Oktira Roka; Aisyah, Iis Nisya Nur; Fitria, Karomah Indah (Universitas Djuanda, 2024)
Strawberries (Fragaria x ananassa Duch.) are a valuable horticultural crop in Indonesia, but their productivity is threatened by anthracnose disease caused by Colletotrichum acutatum Simmonds. Traditional control methods often involved synthetic fungicides, which posed risks of pesticide residues and environmental harm. This study investigated Actinomycetes isolated from various strawberry plant organs and their rhizosphere as potential biological control agents. The isolation processes included the collection of Actinomycetes from strawberry plant organs and the rhizosphere, along with the regeneration of C. acutatum. The isolates were identified through observations of their morphological characteristics. Screening of antagonistic activity was performed using dual-culture assays. Over 10 Gram-positive Actinomycetes strains were successfully isolated and characterized. Two isolates exhibited the highest antagonistic activity against C. acutatum, with inhibition percentages of 67.17% and 55.80%, respectively. Data analysis revealed that these isolates demonstrated significant biocontrol potential through mechanisms such as competition and antibiosis. The results suggested that Actinomycetes could serve as effective, eco-friendly alternatives to chemical pesticides in strawberry cultivation. Future research should focus on optimizing these strains for broader agricultural applications.